Death on the Emerald Isle : a Murder, she wrote mystery - Fletcher, Jessica; Moran, Terrie Farley (Fletcher, Jessica. Murder, she wrote, 2023)
"A trip to Northern Ireland becomes unexpectedly grim for Jessica Fletcher in this new entry in the USA Today bestselling Murder, She Wrote series. Jessica Fletcher is quick to accept an invitation to replace a speaker who couldn't attend a Book Festival in Belfast, Ireland. When her Cabot Cove neighbor Maeve O'Bannon hears about the trip, she asks Jessica to deliver some paintings to her family in the village of Bushmills. Happy to extend her travels and see more of the Irish countryside, Jessica agrees. The festival goes off without a hitch, and it seems like Jessica is in for a relaxing vacation. But then Maeve's cousin Michael is discovered dead under suspicious circumstances. Jessica finds herself once again in the midst of a murder investigation, and she'll have to dig into the O'Bannon family's secrets to unmask the killer."--